Pengaruh short message service (SMS) terhadap pengetahuan dan intensi menyusui di Kabupaten Purbalingga Provinsi Jawa Tengah - Zly Wahyuni; Theodola Baning Rahayujati; Mohammad Hakimi (Fakultas Kedokteran Universitas Gadjah Mada, 2017)
Effect of short message service toward knowledge and breastfeeding intention in Purbalingga district, Central JavaPurposeThis study aimed to determine the effect of short message service on improving mother's knowledge and intention in breastfeeding.MethodsThis study used a quasi-experimental design with non equivalent control group and pretest and posttest conducted with 36 breastfeeding mothers who received a breastfeeding brochure with short message service in the intervention group and 32 breastfeeding mothers who received only the brochure in the control group. The breastfeeding mothers all had an infant less than 2 months old and had a handphone. Data were processed by stata 12.0 using paired t-test, unpaired t-test and linear regression tests.ResultsThe pretest-posttest scores showed increase of knowledge about breastfeeding after delivering information of breastfeeding through short message service (p<0.05). It showed no effect of increasing breastfeeding intention after delivering information of breastfeeding through short message service (p> 0.05).ConclusionShort message service was effective to improve knowledge of breastfeeding mothers, however it had no effect in improving breastfeeding intentions.